Green biosynthesis and characterization of zinc oxide nanoparticles using brown marine macroalga Sargassum muticum aqueous extract - Azizi, Susan; Ahmad @ Ayob, Mansor; Namvar, Farideh; Mohamad, Rosfarizan (Elsevier, 2014)
Biosynthesis of nanoparticles is an important area in the field of nanotechnology which has economic and eco-friendly benefits over chemical and physical methods of synthesis. The present contribution deals with one pot method for synthesis of zinc oxide nanoparticles (ZnO NPs) through green process using the brown marine macroalgae Sargassum muticum (S.muticum) aqueous extract. FTIR spectra revealed the involvement of sulfate and hydroxyl moieties of polysaccharide in the formation of ZnO NPs. Pure ZnO NPs were obtained after calcination of S.muticum formed ZnO at 450 °C. FESEM analysis shows that the pure ZnO NPs synthesized have hexagonal wurtzite structures and the average size ranged from 30 to 57 nm. The UV–vis absorption spectra of the pure ZnO NPs exhibited absorption peaks in the UV region which were attributed to the band gap of the ZnO NPs.